The Emerging Landscape of Long Non-Coding RNAs in Wilms Tumor - Liu, Qiang (Frontiers in Oncology, 2022)
Long noncoding RNAs (LncRNAs) are transcripts of nucleic acid sequences with a length of more than 200 bp, which have only partial coding capabilities. Recent studies have shown that lncRNAs located in the nucleus or cytoplasm can be used as gene expression regulatory elements due to their important regulatory effects in a variety of biological processes. Wilms tumor (WT) is a common abdominal tumor in children whose pathogenesis remains unclear. In recent years, many specifically expressed lncRNAs have been found in WT, which affect the occurrence and development of WT. At the same time, lncRNAs may have the capacity to become novel biomarkers for the diagnosis and prognosis of WT. This article reviews related research progress on the relationship between lncRNAs and WT, to provide a new direction for clinical diagnosis and treatment of WT.